2010
DOI: 10.1002/bem.20631
|View full text |Cite
|
Sign up to set email alerts
|

Deprotonation of glutamic acid induced by weak magnetic field: An FTIR‐ATR study

Abstract: It has been claimed that weak extremely low frequency electromagnetic fields (ELF-EMFs) can affect biochemical reactions and a wide-ranging body of literature is available on this topic. Nevertheless, the physical nature of these effects remains largely unknown. We investigated the influence of ELF-EMF on glutamic acid solutions using Fourier transform infrared-attenuated total reflectance (FTIR-ATR) spectra. Samples were exposed for 10, 20, or 30 min to a weak EMF generated by Helmoltz coils, and then placed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Further details of the experimental apparatus together with a simulation of the field inside the experimental region have been extensively described elsewhere [De Ninno and Congiu Castellano, 2011a]. The homogeneity of the field is guaranteed by the geometrical configuration.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further details of the experimental apparatus together with a simulation of the field inside the experimental region have been extensively described elsewhere [De Ninno and Congiu Castellano, 2011a]. The homogeneity of the field is guaranteed by the geometrical configuration.…”
Section: Methodsmentioning
confidence: 99%
“…The exposure interval has been fixed to 30 min because we have formerly observed that the effect of magnetic field, on solutions of amino acids, is induced in a time longer than 20 min and reaches a saturation in about 30 min [De Ninno and Congiu Castellano, 2011a]. During the exposure, the stability of temperature has been monitored with a thermocouple.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…37,38 Glu has three different ionisable groups, the a-carboxyl group (pK a = 2.2), carboxyl group (pK a = 4.3), a-amino group (pK a = 9.7). 37,38 Glu has three different ionisable groups, the a-carboxyl group (pK a = 2.2), carboxyl group (pK a = 4.3), a-amino group (pK a = 9.7).…”
Section: The Effect Of Ph On Glu Adsorption In [Al(oh)(l)] Nmentioning
confidence: 99%